1609 New Amazing two Lateral Cisor Line Technic with Dual Mesh Repair in Omphalocele. (October 2012) - Vali, M; Ghaffari, R; Macooie, A; Fakoor, Z; Geibi, S; Hijazi, S; Noruzi, M; Ghaffari, H; Ebrahimzadeh, M; Jariani, M; Ghaffari, A; Ghaffari, K; et al.
Abstract : Omphalocele is very disturbing problem in infants with more complication and trouble theraphy that the lesion covered with nylon paper and late repair. This problem so exposed very difficult management and therapy TPN and the intestine are exposed long time out of abdomen and nylon covered can teared so patients stayed long time in hospital.so presentation of new technic with early repair and soft cover is nessessary .For this from 3yrs ago the 10 neonate are surgeried with dual mesh.with initial repair of omphalocele in supine position that one edge of foam like mesh is sutured to abdominal wall and other soft edge overlied omphalocele contents with skin flap covered all them finally and two lateral cisor was done and in 1–3 yrs f/u the all 10 neonate that the oldest 3yrs old and youngest 6mo old nowadays are in health. This way is easy, safe with less TPN and hospital staying and more best results. The dual mesh was been same with abdominal wall without any complication. The study was done prospective and with dual mesh and CT scan 16 slice in control of them was done. The dual mesh was been same with abdominal wall.